The Hırvatalı Mehmet Ağa Revolt in Terms of Kurdish-Nestorian Relations - Sabri Deniz, Mehmet (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The “Hırvatalı Mehmet Ağa Rebellion”, which was effective in Hakkari and its surroundings during the Crimean War, took a wide place in the archive documents of the period. During the war, Russia came into close contact with the Kurdish and Nestorian tribes residing in the region in order to occupy the Hakkari environs. As a result of this contact, Kurdish and Nestorian tribes rebelled against the Ottoman central authority and indirectly against England under the leadership of Croatian Mehmet Ağa and Patriarch Mar Şimun, allied with Russia, which they thought was the new ruler of the region. During the rebellion, Kurdish and Nestorian tribes acted together. The rebellion is remarkable because it took place shortly after Bedirhan Bey’s military operations against the Nestorians of Hakkâri.